2016
DOI: 10.3892/ol.2016.4153
|View full text |Cite
|
Sign up to set email alerts
|

Laricitrin suppresses increased benzo(a)pyrene-induced lung tumor-associated monocyte-derived dendritic cell cancer progression

Abstract: Abstract. Benzo(a)pyrene (BaP) stimulates lung cancer cells, promoting monocyte-derived dendritic cells to secrete soluble factors, including heparin binding-epidermal growth factor and C-X-C motif chemokine 5. The secretions from monocyte-derived dendritic cells stimulate the progression of lung cancer cells, including the migration and invasion of cells. To the best of our knowledge, these secretions remain unknown, and require additional study. The present study identified that treatment with BaP-H1395-tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Peripheral monocytes leave the bloodstream and migrate into tissues where, following conditioning by local growth factors, both microbial products and pro-inflammatory cytokines can differentiate into tissue macrophages and dendritic cells populations [ 33 ]. In addition, many studies reported that these cells can produce and secrete various cytokines to promote tumorigenesis, cancer progression and metastasis [ 27 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral monocytes leave the bloodstream and migrate into tissues where, following conditioning by local growth factors, both microbial products and pro-inflammatory cytokines can differentiate into tissue macrophages and dendritic cells populations [ 33 ]. In addition, many studies reported that these cells can produce and secrete various cytokines to promote tumorigenesis, cancer progression and metastasis [ 27 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the bioactive component of grape seeds has also been found to potentiate anti-cancer activity of doxorubicin via an immunomodulatory mechanism [ 17 ]. Laricitrin, syringetin, resveratrol and piceatannol, are phenolic compounds found in red grapes and Vaccinium uliginosum L [ 18 , 19 ]. This study demonstrates that laricitrin provides the highest level of efficacy to improve lung cancer-mediated DC suppression through the down-regulation of the STAT3/IL-10 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…When BaP is released into the air, it can move into the atmosphere, land, or water (16). In addition to the well-known mutagenic and carcinogenic effects of BaP on the pulmonary cells in both animals and humans (17)(18)(19)(20)(21)(22), accumulating data have indicated that BaP is toxic to the female reproductive system (23)(24)(25)(26)(27). It has been reported that significantly increased levels of BaP are found in the follicular fluid of female smokers, who have more exposure to PAHs than nonsmoking people (28).…”
mentioning
confidence: 99%